Learning Strategies In Speaking By The Students Of SMK Sahid Surakarta (A Case Study) - Budiarti, Agustin (2012)
This research has a purpose to describe the learning strategies used by the students of SMK Sahid Surakarta in mastering English speaking skill. The result of this study hopefully will give contribution in learning English especially in speaking English. This research studies about learning strategies in speaking by the students of SMK Sahid Surakarta (a case study). The type of this research is descriptive qualitative research with case study which aims at describing the learning strategies in speaking skill of SMK Sahid Surakarta. The subjects of this research are two students chosen based on the recommendation of the teacher, the score of the speaking subject. The methods of collecting data are interview, observation, and documentation. The data are taken from the subjects of the research in the form of interview, observation and documentation. The result of this research shows that the students of SMK Sahid Surakarta use almost all of learning strategies proposed by O'Malley and Chamot. Their attention and action in learning are different. The students of SMK Sahid Surakarta use five metacognitive strategies, namely advance organizer, directed attention, selective attention, self management and self-evaluation. There are two various learning strategies used the students of SMK Sahid Surakarta. They are six cognitive strategies; repetition, resourcing, imagery, elaboration, note taking and recombination, and then five cognitive strategies; repetition, resourcing, imagery, elaboration and note taking. And the last, they use two social-affective strategies; cooperation and question for clarification, and then only one socialaffective strategy that is cooperation. Finally, the writer concludes that all learning strategies which are important to improve the learner's speaking skill are; advance organizer, directed attention, selective attention, self management, self-evaluation, repetition, resourcing, imagery, elaboration, note taking, recombination, cooperation and question for clarification